A moderate autoethnography: exploring ACEs, transitions, military service, and teaching - Meritt, Dustin Deane (Kansas State University, 2023)
“Write straight into the emotional center of things…write toward vulnerability.” – Anne Lamott “You’re just not college material.” At 17 years old, these words, spoken by my school’s academic counselor, concisely summarized my school experience. As a struggling student with a turbulent home life, this statement launched me on the path from struggling student to Army soldier to veteran transitioning into civilian life to teacher. Through triumphs and tribulations, each of these phases and transitions has significantly shaped who I am today. This study of personal experience narratives explores my journey through youth, military service, and educator. I will share the intimate struggles that occurred: exposure to abuse, addiction, parent separation, infidelity, divorce, financial strain, homelessness, and mental health battles. The narratives weave in and out of transitional periods and connections to social and cultural experiences. This lens also examines literature, theory, and publication. To say that this research study has been life changing is an understatement. Never had I thought that I would attempt—let alone complete—this type of work. It truly started with the advice to “just start writing,” which was echoed by Nash and Bradley (2011) who said “to get started writing, you must get your butt in the chair” (p.39). I have always had stories to tell about my unique factors and experiences in my past. What I did not know was what could come out of them once they were analyzed. Writing about the past has been difficult, but applying a methodology, lens, and various frameworks has provided an avenue for some explanation. Although it may be a research methodology revolved around the power of one, choosing autoethnography, like any other design, takes careful planning (Chang, 2016). I would argue because of the potential vulnerability of the author, and possibly others, more attention to detail in ethics and validity becomes a virtuous quest in the process. This is not an autobiography, it is an autoethnography, and results that came from it have the potential to be impactful.
Keywords: Transition; Military; Adverse childhood experiences; Culture; Social identity; Veteran